Gene Expression Profile in Delay Graft Function: Inflammatory Markers Are Associated with Recipient and Donor Risk Factors. (18th May 2014) - Guerrieri, Diego; Re, Luis; Petroni, Jorgelina; Ambrosi, Nella; Pilotti, Roxana E.; Chuluyan, H. Eduardo; Casadei, Domingo; Incardona, Claudio
Abstract : Background. Delayed graft function (DGF) remains an important problem after kidney transplantation and reduced long-term graft survival of the transplanted organ. The aim of the present study was to determine if the development of DGF was associated with a specific pattern of inflammatory gene expression in expanded criteria of deceased donor kidney transplantation. Also, we explored the presence of correlations between DGF risk factors and the profile that was found. Methods. Seven days after kidney transplant, a cDNA microarray was performed on biopsies of graft from patients with and without DGF. Data was confirmed by real-time PCR. Correlations were performed between inflammatory gene expression and clinical risk factors. Results. From a total of 84 genes analyzed, 58 genes were upregulated while only 1 gene was downregulated in patients with DGF compared with no DGF (P = 0.01 ). The most relevant genes fold changes observed was IFNA1, IL-10, IL-1F7, IL-1R1, HMOX-1, and TGF-β . The results were confirmed for IFNA1, IL-1R1, HMOX-1 and TGF-β . A correlation was observed between TGF-β, donor age, and preablation creatinine, but not body mass index (BMI). Also, TGF-β showed an association with recipient age, while IFNA1 correlated with recipient BMI. Furthermore, TGF-β, IFNA1 and HMOX-1 correlated with several posttransplant kidney function markers, such as diuresis, ultrasound Doppler, and glycemia. Conclusions. Overall, the present study shows that DGF is associated with inflammatory markers, which are correlated with donor and recipient DGF risk factors.